Strengthening Construction Service Development Strategy Through a Comprehensive Business Ecosystem Approach - Syarif Muhammad; Dodi Tricahyono (LPPM Institut Bisnis dan Informatika Kesatuan, 2025)
The contribution of construction services in Indonesia is quite large, where in the first quarter of 2024 it contributed 7.59 of the total gross domestic product. In the last decade, the construction industry has undergone major changes. From the beginning, the competition was not too fierce, with a few large companies dominating the market. This industry is growing rapidly. The three main problems faced by entrepreneurs are the high level of competition, the declining demand for construction services, and the fluctuating price of building materials. The same thing happened to PT Wijaya Karya Industri & Konstruksi (WIKON), which is engaged in construction services. The decline in demand for construction services has had an impact on the acquisition of contract turnover, revenue, and profit and loss at PT WIKON has decreased from 2021 to 2023. This research aims to identify the actors involved, to understand the interaction between actors, so that it can provide an overview or recommendations about what is needed by the company to develop the construction heavy equipment business. This study uses a business ecosystem approach with a qualitative method conducted through data collection, literature studies, and in-depth interviews to map it using the ecosystem approach.